Limited Clinical Utility of Follow-up Blood Cultures in Patients With Streptococcal Bacteremia: An Opportunity for Blood Culture Stewardship. (7th November 2020) - Siegrist, Emily A; Wungwattana, Minkey; Azis, Leyla; Stogsdill, Patricia; Craig, Wendy Y; Rokas, Kristina E
Abstract: Background: The value of positive follow-up blood cultures (FUBCs) in streptococcal bacteremia has not been well defined. Therefore, we explored the frequency of and risk factors for positive FUBC in a retrospective cohort of patients with streptococcal bacteremia. Methods: Adults ≥18 years of age, admitted with at least 1 positive blood culture for Streptococcus spp between 2013 and 2018 followed by at least 1 FUBC, were potentially eligible. Positive FUBCs were defined as cultures positive for the same streptococcal species drawn >24 hours after the index culture. We excluded patients with polymicrobial bacteremia. We compared the characteristics of patients with and without a positive FUBC. Results: In our single-center cohort, we identified 590 patients with streptococcal bacteremia, and 314 patients met inclusion criteria. Ten patients had FUBC with Streptococcus spp (3.2%), 4 (1.3%) had a contaminant identified, and 3 (1.0%) had a new pathogen isolated. Endocarditis (5 of 10 [50.0%] vs 35 of 304 [11.5%]), epidural abscess (2 of 10 [20%] vs 4 of 304 [1.3%]), and discitis or vertebral osteomyelitis (3 of 10 [30.0%] vs 14 of 304 [4.6%]) were associated with positive FUBC. Patients with positive FUBC had a longer median length of stay (12.9 vs 7.1 days, P  = .004) and longer duration of antibiotic treatment (14.9 vs 43.2 days, P  = .03). Conclusions: Follow-up blood cultures among patients with streptococcal BSI are rarely positive. Clinicians could consider limiting follow-up blood cultures in patients at low risk for deep-seated streptococcal infections, persistent bacteremia, or endovascular infection. Abstract : Patients with streptococcal bacteremia infrequently have positive follow-up blood cultures (FUBCs). Endocarditis, epidural abscess, and discitis or vertebral osteomyelitis are associated with positive FUBC. Clinicians should consider limiting orders for FUBC when patients have low risk for severe streptococcal infections.